2006
DOI: 10.1111/j.1439-0388.2006.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of somatic cell score in dairy cattle considering first and later lactations as two different but correlated traits

Abstract: A test-day (TD) random regression model (RRM) was described for the genetic evaluation of somatic cell score (SCS) where first and later lactations were considered as two different but correlated traits. A two-step covariance function procedure was used to estimate variance-covariances and associated genetic parameters. Analysis of estimated breeding values (EBV), ranking of top bulls and cows and some computational aspects were used to compare RRM with TD repeatability model (RPM) and lactation average model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
25
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 34 publications
12
25
1
Order By: Relevance
“…The lowest correlations within lactation were between the 5 th and the 305 th day of lactation, and they were equal to 0.21, 0.29, 0.29 for the first, second and third lactation, respectively. This was in agreement with other studies, in which the lowest genetic correlations were between SCS at the most distant TD (Haile-Mariam et al, 2001;Koivula et al, 2002;Odegard et al, 2003;Koivula et al, 2004;Negussie et al, 2006). The estimates ranged from 0.33 to 0.71 for the first lactation (Haile-Mariam et al, 2001;Odegard et al, 2003;Koivula et al, 2004) and were higher than in the present study.…”
Section: Heritabilitysupporting
confidence: 69%
See 3 more Smart Citations
“…The lowest correlations within lactation were between the 5 th and the 305 th day of lactation, and they were equal to 0.21, 0.29, 0.29 for the first, second and third lactation, respectively. This was in agreement with other studies, in which the lowest genetic correlations were between SCS at the most distant TD (Haile-Mariam et al, 2001;Koivula et al, 2002;Odegard et al, 2003;Koivula et al, 2004;Negussie et al, 2006). The estimates ranged from 0.33 to 0.71 for the first lactation (Haile-Mariam et al, 2001;Odegard et al, 2003;Koivula et al, 2004) and were higher than in the present study.…”
Section: Heritabilitysupporting
confidence: 69%
“…For the third parity, Haile-Mariam et al (2001) reported very low genetic correlations between the beginning and the end of lactation (0.14). Koivula et al (2002) and Negussie et al (2006) reported that within lactation genetic correlations were higher in the first than in the second lactation, which was not confirmed in our study.…”
Section: Heritabilitycontrasting
confidence: 56%
See 2 more Smart Citations
“…Thus, for genetic evaluation of animals, a MT model treating first and later lactations as different but correlated traits would be a practical strategy. Negussie et al (2006) described a method of treating first and later lactations as two different traits in genetic evaluation of SCS in dairy cows.…”
Section: Genetic Correlations Between Scs and CMmentioning
confidence: 99%